To Prevent Discrimination by Boards of Trade Against Farmers' Cooperative Associations. hearings before the United States House Committee on Agriculture, Sixty-Ninth Congress, first session, on Apr. 12, 1926. (U.S. Congressional Hearings., 1926)
Committee Serial K -- Part 1.